Coexistence of secondary syphilis with psoriasis - Gwiazdowska, Anetta; Brzezicka-Ciach, Urszula; Sobieszek-Kundro, Anna (Dermatology Review/Przegląd Dermatologiczny, 2010)
Introduction . Psoriasis is an inflammatory skin disease of chronic course with remissions and exacerbations provoked by various exogenous factors comprising infections. Syphilis is an infectious disease which can mimic many chronic dermatoses and be a cause of diagnostic difficulties. Objective . To present difficulties in the diagnosis of secondary syphilis in a patient with psoriasis. Case report . A 22-year-old male patient with type I psoriasis manifested acute eruption of psoriasiform papules which were resistant to topical anti-psoriatic therapy. Detailed case history and results of serological investigations allowed a diagnosis of secondary syphilis to be made. Skin lesions went to remission during the treatment with procaine penicillin (1.2 ml/day). Conclusions . Our case shows that in cases of chronic skin diseases, especially with atypical morphological presentation and resistant to treatment, serological tests for syphilis should be performed.